Evaluating the Iron Deficiency Anemia in Type-II Diabetic Patients Taking Metformin and its Association with Oxidative Stress - Umer, Abdullah; Sarfraz, Junaid; Ahmed, Hateem; Abdul Qayyum, Rao; Parveen, Aamira; Manan, Zarwa; Qammar, Bilal (Indus Journal of Bioscience Research, 2024)
Introduction: Iron deficiency anemia (IDA) is a prevalent nutritional deficiency worldwide, particularly affecting vulnerable groups with chronic illnesses, such as type 2 diabetes mellitus (T2DM). T2DM, characterized by insulin resistance and hyperglycemia, impacts numerous physiological processes and is linked with increased oxidative stress. Objective: This study aims to examine the prevalence of iron deficiency anemia in T2DM patients taking metformin and to investigate its association with oxidative stress. Methodology: Conducted at Shalamar Hospital, Lahore, this cross-sectional study took place from September 2023 to September 2024 and included 255 patients aged 30–70 years. Exclusion criteria were patients with chronic kidney disease, liver dysfunction, gastrointestinal disorders affecting nutrient absorption, or those taking iron supplements or medications influencing iron metabolism. Results: Among the participants, 40.9% (92 patients) were diagnosed with IDA, with a mean hemoglobin level of 11.5 g/dL. In contrast, 59.1% (133 patients) without IDA had a higher mean hemoglobin of 14.3 g/dL. IDA patients showed significantly elevated malondialdehyde (MDA) levels at 3.8 μmol/L, compared to 2.5 μmol/L in non-IDA patients (p < 0.05), suggesting increased lipid peroxidation. Antioxidant enzyme levels were also lower in the IDA group, with superoxide dismutase (SOD) and glutathione peroxidase (GPx) at 150 U/mL and 80 U/mL, respectively, versus 200 U/mL and 100 U/mL in non-IDA patients. Conclusion: This study concludes that iron deficiency anemia is common among T2DM patients on metformin and is significantly associated with increased oxidative stress